2019
DOI: 10.2147/rrtm.s208473
|View full text |Cite
|
Sign up to set email alerts
|

<p>Impact of annual preventive mass chemotherapy for soil-transmitted helminths among primary school children in an endemic area of Gurage zone: a prospective cross-sectional study</p>

Abstract: Background and aim School-based preventive mass chemotherapy has been a key component of Ethiopia's national plan for the control of soil-transmitted helminths. Without an impact evaluation on the impact of a deworming program on infection levels, it is unclear whether the deworming program warrants levels of environmental transmission of infection. This study aimed to determine the impact of annual preventive mass chemotherapy for soil-transmitted helminths among schoolchildren in an endemic area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…The result of this study illustrates the importance of addressing the community-based reservoir to reduce the reinfections of the treated children and other at-risk populations through expanding the target population, integrated with health and hygiene education and the provision of adequate sanitation facilities [ 31 , 32 , 34 ]. A study conducted among agrarian communities of Kogi State, Nigeria recommends the inclusion of all age groups in preventive chemotherapy along with health education and provision of basic sanitation facilities to eliminate STH and break their transmission by 2025 [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of this study illustrates the importance of addressing the community-based reservoir to reduce the reinfections of the treated children and other at-risk populations through expanding the target population, integrated with health and hygiene education and the provision of adequate sanitation facilities [ 31 , 32 , 34 ]. A study conducted among agrarian communities of Kogi State, Nigeria recommends the inclusion of all age groups in preventive chemotherapy along with health education and provision of basic sanitation facilities to eliminate STH and break their transmission by 2025 [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This implies that if the infected adult populations of the community are left untreated, they may serve as an important reservoir and source of re-infection for the treated children, contributing to the sustained transmission of the STH in the community. Previous studies conducted in various countries have shown that STH reinfections occur rapidly after treatment, particularly for A. lumbricoides and T. trichiura, and hence have a significant impact on the success of preventive mass chemotherapy [31][32][33][34][35].…”
Section: Plos Onementioning
confidence: 99%
“…Series of studies have reported the effectiveness of chemotherapy in control of STH infection especially when done annually. A study in Gurage Zone, Ethiopia [ 39 ], reported that chemotherapy results in substantial reduction in overall prevalence and intensity of STHs. The residual infections with STHs in this study are a reflection of the maintenance of transmission among the untreated populations in the community which are constantly in contact with the dewormed children.…”
Section: Discussionmentioning
confidence: 99%
“…Series of studies have reported the effectiveness of chemotherapy in control STHs infection especially when done annually. A study in Gurage Zone, Ethiopia [31] reported that chemotherapy results in substantial reduction in overall prevalence and infection intensity of STHs. The residual infections with STHs in this study is a re ection of the maintenance of transmission among the untreated populations in the community which are constantly in contact with the dewormed children.…”
Section: Discussionmentioning
confidence: 99%